Public health risk assessment for human exposure to chemicals - Asante-Duah, D. Kofi (Springer, 2017)
This book provides a concise, yet comprehensive overview of the many facets relating to human health risk assessments in relation to chemical exposure problems. It presents some very important tools and methodologies that can be used to address chemical exposure and public health risk management problems in a consistent, efficient, and cost-effective manner. On the whole, the book represents a collection and synthesis of the principal elements of the risk assessment process that may be used to more effectively address issues pertaining to human exposures to chemicals found in modern societies. This also includes an elaboration of pertinent risk assessment concepts and techniques/methodologies for performing human health risk assessments. Written for both the novice and the experienced, the subject matter of this book is an attempt at offering a simplified and systematic presentation of public health risk assessment methods and application tools? all these facilitated by a layout that will carefully navigate the user through the major processes involved. A number of illustrative example problems are interspersed throughout the book, in order to help present the book in an easy-to-follow, pragmatic manner.
Keywords: Health risk assessment.; Environmental toxicology.; elektronické knihy; electronic books